Assessment of clinical risk factors for drug-resistant epilepsy in children and teenagers - Kasprzyk, Marta; Brola, Waldemar; Wendorff, Janusz (Medical Studies/Studia Medyczne, 2014)
Introduction: Epilepsy is one of the most common neurological illnesses occurring in children. In approximately 20–30% of cases it is drug-resistant. Aim of the research: To assess the already-known risk factors, analyse the rarely described ones, and find new causes of epilepsy drug resistance in children, taking into account the level of impact of each factor. Material and methods : The study comprised 152 of all 383 children hospitalised in 2012 at the Neurology Department of the Polish Mother’s Memorial Hospital in Lodz due to epilepsy. Based on medical documentation, neurological examination, and our own questionnaire, we divided patients into two groups: drug-resistant epilepsy or drug-sensitive epilepsy. We compared the type, level of influence, and prevalence of different factors. For statistical analysis, the 2 test was used. Statistical significance was set at p < 0.05. Results: Drug-resistant epilepsy was found in 64 patients (42.1%), and drug-sensitive epilepsy was found in 88 patients (57.9%). Factors that were most probable to cause drug resistance included: high prevalence of seizures (Cramer’s V = 0.66), type of epileptic syndrome (V = 0.62), psychomotor developmental delay (V = 0.62), and occurrence of status epilepticus (V = 0.6). Factors such as infections of CNS in early childhood, repeated severe infections of airways in childhood, and mother’s infectious diseases with high fever during pregnancy were rare or non occurring (Cramer’s V = 0.41, 0.32, and 0.31, respectively). Conclusions : The study confirmed the previously known causes of drug resistance and indicated the significance of underestimated inflammatory and infectious factors involving pyrexia, in children and also in mothers during pregnancy.